PENGARUH KEPUASAN KERJA, KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASIONAL PADA KINERJA KARYAWAN, DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) SEBAGAI VARIABEL MEDIASI - Supriyanto, Agus (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2014)
This study aims to determine the effect of job satisfaction, transformational leadership and organizational commitment on employee performance, using OCB as mediating variable. This research was conducted on employees at PT. Dan Liris Sukoharjo Central Java. The respondents were regular employees totaling 200 employees. The technique of sampling was Non-Probability Sampling and the technique of analyzing data was Structural Equation Modeling (SEM) using AMOS 21.0 program. The result shows that job satisfaction, transformational leadership, organizational commitment and OCB simultaneously give positive effect and significant on the employeesâ performance. Job satisfaction and organizational commitment on OCB is not significant, whereas transformational leadership give positive effect and significant on OCB. OCB success to mediate the full effect between job satisfaction and organizational commitment on employee performance, but OCB mediates the influence of transformational leadership on employee performance partially. Managerial implications of this research are human resource management should improve job satisfaction, organizational commitment and appealedthe head to apply transformational leadership to improve employee performance through OCB behaviors.